The inclusion of people with disabilities (PDC) - a nonexistent dialogue with organizational theory (Research, Society and Development, 2021)
Advances in the legislation of contemporary societies have enabled new perspectives on minorities. The Brazilian State contemplated social groups victimized by some form of excluding participation, such as quota systems, a mechanism used to promote the inclusion of people with disabilities (PDC). Thus, it is worth remembering that people with disabilities have always been on the sidelines of the process of inclusion and citizenship, being restricted even from their right to life. The problem question seeks an understanding of the existence or not of a conceptual fabric (beyond the legal field), which can integrate the inclusion of people with disabilities (PCD’s), with the bases of organizational theory, with the world of work (behavior and dynamics of companies) and with the social responsibility of companies, in order to effectively welcome people with disabilities and understand their contributions to business activities? The objective is to analyze the existence of this integrated conceptual fabric, capable of providing a better understanding of the constructs and legal aspects that define people with disabilities and their inclusion, in the field of organizational theory and social responsibility, in order to better clarify the integrative assumptions for inclusion of people with disabilities in the world of work (field of business dynamics). The research has a descriptive/exploratory nature. Its main results are summarized in the aspects of an inclusion of PCD still restricted to the legal field, with a total exclusion of the theme by organizational theory and inclusion in the business field, still being legitimized by a concept of social responsibility, which staggers, oscillates between real responsibility and fad.